Noninvasive ventilation with a helmet in patients with acute respiratory failure caused by chest trauma: a randomized controlled trial - Qi Liu (Nature Portfolio, 2020)
Abstract Noninvasive ventilation (NIV) is beneficial in acute respiratory failure (ARF) caused by chest trauma; however, NIV-related complications affect the efficacy. We evaluated whether NIV with helmet decreases the incidence of complications and improves its effects in a single center. Patients with ARF after chest trauma were randomized to receive NIV with helmet or face mask. The primary outcome was the rate of NIV-related complications. Secondary outcomes were PaO2/FiO2, patient’s tolerance, intubation rate, length of intensive care unit (ICU) stay, and ICU mortality. The trial was terminated early after an interim analysis with 59 patients. The incidence of complications was lower in the helmet group [10% (3/29) vs 43% (13/30), P = 0.004], and PaO2/FiO2s were higher at 1 h and at the end of NIV (253.14 ± 64.74 mmHg vs 216.06 ± 43.86 mmHg, 277.07 ± 84.89 mmHg vs 225.81 ± 63.64 mmHg, P = 0.013 and 0.012) compared with them in face mask group. More patients reported excellent tolerance of the helmet vs face mask after 4 h of NIV [83% (24/29) vs 47% (14/30), P = 0.004] and at the end of NIV [69% (20/29) vs 30% (9/30), P = 0.03]. Differences in intubation rate, ICU stay, and mortality were non-significant (P = 0.612, 0.100, 1.000, respectively). NIV with helmet decreased NIV-related complications, increased PaO2/FiO2, and improved tolerance compared with NIV with face mask in patients with chest trauma. Trial registration: Registered in the Chinese Clinical Trial Registry (ChiCTR1900025915), a WHO International Clinical Trials Registry Platform ( http://www.chictr.org.cn/searchprojen.aspx ).